Faktor Pendorong Mahasiswa Bermain Game Online Mobile - Yakub Buruja Karim; Maura Novandi; Aldin Ramadhani; Jihad Lukis Panjawa (UNISBA Press, 2023)
Abstract. Evidence of the rapid development of technology is the widespread use of the internet, one of which is mobile online games. Mobile online games are not only used for gaming purposes, but also for business and profession. The purpose of this research is to analyze the driving factors for student goals in playing mobile online games for entertainment or business and professional purposes. Based on the research, the results obtained in the form of variable effort expectancy, social influence, and habit have no significant effect on business and profession as the goal of students playing online mobile games. The government is expected to create a program that accommodates students who make online mobile games a business or profession. Abstrak. Bukti pesatnya perkembangan teknologi adalah meratanya penggunaan internet, salah satunya game online mobile. Game online mobile tidak hanya digunakan untuk keperluan bermain game saja, melainkan juga untuk bisnis dan profesi. Tujuan adanya penelitian ini adalah untuk menganalisis faktor pendorong tujuan mahasiswa bermain game online mobile untuk keperluan hiburan atau bisnis dan profesi. Berdasarkan penelitian didapatkan hasil berupa variable effort expectancy, social influence, dan habit tidak berpengaruh signifikan terhadap bisnis dan profesi sebagai tujuan mahasiswa bermain game online mobile. Pemerintah diharapkan dapat membuat suatu program yang mewadahi mahasiswa yang menjadikan game online mobile sebagai bisnis atau profesi.